2013
DOI: 10.1105/tpc.113.111096
|View full text |Cite
|
Sign up to set email alerts
|

Cell Growth Defect Factor1/CHAPERONE-LIKE PROTEIN OF POR1 Plays a Role in Stabilization of Light-Dependent Protochlorophyllide Oxidoreductase in Nicotiana benthamiana and Arabidopsis    

Abstract: Angiosperms require light for chlorophyll biosynthesis because one reaction in the pathway, the reduction of protochlorophyllide (Pchlide) to chlorophyllide, is catalyzed by the light-dependent protochlorophyllide oxidoreductase (POR). Here, we report that Cell growth defect factor1 (Cdf1), renamed here as CHAPERONE-LIKE PROTEIN OF POR1 (CPP1), an essential protein for chloroplast development, plays a role in the regulation of POR stability and function. Cdf1/CPP1 contains a J-like domain and three transmembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…Seeds of the Atcdf1 mutant GK-852F12-025757 were obtained from GABI-Kat (www.gabi-kat.de) but did not provide viable plants, consistent with previous results (20,23). To study the impact of CDF1 deficiency in vivo, we therefore used DEX-inducible RNAi, as described by Lee et al (23).…”
Section: Methodsmentioning
confidence: 64%
See 4 more Smart Citations
“…Seeds of the Atcdf1 mutant GK-852F12-025757 were obtained from GABI-Kat (www.gabi-kat.de) but did not provide viable plants, consistent with previous results (20,23). To study the impact of CDF1 deficiency in vivo, we therefore used DEX-inducible RNAi, as described by Lee et al (23).…”
Section: Methodsmentioning
confidence: 64%
“…CDF1 proteins have no reported homology with any known animal protein, except for the presence of a J-like domain characteristic of DnaJ/Hsp40-type cochaperones (21,22). Hydrophobicity analyses revealed that CDF1 and the protein encoded by At3g51140 contain three trans-membrane domains, whereas other CDF1-related proteins, including Synechocystis slr1918 and At2g20920, possess four trans-membrane domains (19,20,23). …”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations